POLITIK PERIZINAN USAHA TOKO MODERN (RITEL ALFAMART DAN INDOMARET) DI KABUPATEN INDRAGIRI HULU TAHUN 2018 - Sinta Bella Ereta; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Modern Stores (Alfamart and Indomaret Retail) is one of the Modern Stores that stands in Indragiri Hulu Regency. Alfamart and Indomaret Retail Licensing is one of the methods used by the Indragiri Hulu Regency Government in bringing in investors to invest, so that it will increase the positive trend in Regional Original Income. However, in the Alfamart and Indomaret Retail licensing sector, which is run by the Indragiri Hulu Regency Government, it is not only increasing local revenue, but also paying attention to the socio-economic conditions of the people in Indragiri Hulu Regency. This is because it is still not precise to establish Modern Stores (Retail Alfamart and Indomaret) in Indragiri Hulu Regency. The formulation of the problem in this research is who are the actors involved in the business licensing process; what are the interests of the actor; what is the social / institutional basis; and what resources do actors have in the process of licensing the Modern Store business (Alfamart and Indomaret retails) in Indragiri Hulu 2018? This research aims to describe the actors and interests of actors, as well as to describe the social / institutional basis and resources of actors in the Shop Business Licensing process. Modern (Alfamart and Indomaret Retail) in Indragiri Hulu Regency. This study uses a qualitative approach with a descriptive type of approach. The data collection techniques used are interviews and documentation. The data analysis in this study uses the Advocacy Coalition Freamwork. The results of this study are the licensing politics of Modern Stores (Alfamart and Indomaret Retail) in Indragiri Hulu Regency as efforts to provide a safe and comfortable licensing climate for business actors. However, in licensing Modern Stores (Retail Alfamart and Indomaret) in Indragiri Hulu Regency is still not running optimally, this is due to the inconsistency of actors in carrying out their main duties and functions in licensing shop business Modern. Keywords : Actors And Goals, Actor's Interests, Social Base